A full-solid-waste gel-toughened composite material and a preparation method thereof
Patent Information
- Application Number
- CN202511461723.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-10-14
AI Technical Summary
[0002]现有高延性水泥基材料在湿喷应用中普遍存在回弹率高、厚喷易流挂、泵送不稳等问题;同时以水泥为主胶凝导致碳排较高
1)本发明将“可喷性”参数化:以流变-喷射-力学的指标链条给出可复现条件;2)本发明材料耦合机制清晰:PC-SS降低f-CaO、引入碳酸盐核并缓释Ca2+;铝源固废与脱硫石膏形成AFt/AFm早期骨架,提高停喷抗流挂;触变微纳骨架提供可重构网,在泵送与喷射的剪切过程中快速恢复;3)本发明施工适配性强:在常见喷射装备与参数下即可达到低回弹厚喷成型。
Smart Images

Figure CN121159218B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of tunnel repair and reinforcement technology in civil engineering, specifically to a tough all-solid waste gel composite material and its preparation method, and more particularly to a sprayable tough all-solid waste gel composite material and its preparation method. Background Technology
[0002] Existing high-ductility cement-based materials generally suffer from problems such as high rebound rate, easy sagging when sprayed thickly, and unstable pumping in wet spraying applications; at the same time, the cement-based cementitious structure leads to high carbon emissions. Existing "solid waste to replace cement" solutions usually focus on mix ratio replacement and conventional mechanical properties, without providing parameterized definitions of the sprayable window and its functional relationship with chemical ratio, particle size distribution, and thixotropic skeleton, making it difficult to achieve both stable construction and high ductility in wet spraying scenarios.
[0003] High-strength, ultra-high-performance concrete (ECC) is a type of bendable concrete made by using fibers as reinforcing and toughening components, and cement, mineral admixtures, ultrafine aggregates, and additives as matrix raw materials, through mixing with water, molding, and curing. ECC possesses excellent toughness, seismic resistance, and durability, overcoming the inherent brittleness of ordinary concrete. It is an ideal engineering material for improving the toughness of underground spaces and enhancing disaster prevention and mitigation capabilities. Cement is currently the core gelling material for ECC. my country's cement industry accounts for approximately 14% of the country's total carbon emissions and about 75% of the total energy consumption of the national building materials industry. However, the manufacture of concrete has long inevitably involved the use of high-energy-consuming and high-emission cement. Therefore, carbon emission reduction in the cement and concrete industry is a critical issue that must be addressed. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a robust and tough all-solid waste gel composite material and its preparation method, which enables the material to maintain high strength and ductility while achieving low resilience, non-sagging during thick spraying, and stable pumping, and is expressed in a quantifiable parameter window.
[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention discloses a toughened composite material made entirely of solid waste gel, comprising solid waste cementitious material, fine aggregate, water-reducing agent, polyvinyl alcohol fiber, and thixotropic skeleton additive. The solid waste gel material comprises pre-carbonized steel slag powder, granulated blast furnace slag, desulfurized gypsum, and aluminum-derived solid waste. The thixotropic skeleton additive is at least one of attapulgite, sepiolite, and nanocellulose.
[0006] Preferably, the pre-carburized steel slag powder contains f-CaO ≤ 1.0 wt% and CO3 calculated as CaCO3. 2-The content is 8-15 wt%, and the D50 is 2-8 μm; the content of Al2O3 in the aluminum source solid waste is 20-45 wt%.
[0007] Preferably, in the all-solid waste gel material, the molar ratio of SO3 / Al2O3 is 0.8-1.4, and the molar ratio of CaO / (SiO2+Al2O3) is 0.9-1.3.
[0008] Preferably, the aluminum source solid waste is one or more of the following: calcined tap water sludge ash, calcined kaolin, and red mud fine powder; wherein the calcined kaolin is obtained by calcining kaolin at 700-800℃ for 2.5h, and the calcined tap water sludge ash is obtained by calcining sludge ash and red mud fine powder at 550-750℃ for 2.0h respectively, and then mixing them together.
[0009] Preferably, when the thixotropic framework additive is attapulgite, its D50 is 0.2-2 μm and its specific surface area is ≥150 m². 2 / g; when the thixotropic skeleton additive is nanocellulose, its fiber diameter is 10-100 nm and its aspect ratio is ≥100.
[0010] Preferably, the total solid waste cementitious material weighs 1200-1420 kg / m³. 3 Fine aggregate 460-520kg / m³ 3 Water-reducing agent 0-20kg / m 3 Polyvinyl alcohol fiber 5-30kg / m 3 The thixotropic skeleton additive is 0.05-0.30 wt% of the total solid waste cementitious material; the total solid waste cementitious material has a D50 of 4-20 μm and a specific surface area of 400-600 m². 2 / kg.
[0011] Preferably, by mass fraction, the solid waste cementitious material comprises 8-20 parts of pre-carbonized steel slag powder, 50-70 parts of granulated blast furnace slag, 15-30 parts of desulfurized gypsum, and 2-8 parts of aluminum source solid waste.
[0012] Preferably, the volume fraction of the polyvinyl alcohol fiber is 0.5-3.0%, the fiber diameter is 35-40 μm, the length is 9-12 mm, and the strength is ≥1200 MPa.
[0013] Accordingly, a method for preparing a solid waste gel-reinforced composite material includes the following steps: (1) Steel slag powder is subjected to gas-solid pre-carbonization treatment at 25-60℃, CO2 volume fraction of 10-100%, and 30-180 min until f-CaO≤1.0 wt% and CO3 calculated as CaCO3. 2-With a content of 8-15 wt%, pre-carburized steel slag powder is obtained; (2) The granulated blast furnace slag, pre-carbonized steel slag powder, aluminum source solid waste, desulfurized gypsum and fine aggregate are dry mixed, then water and water-reducing agent are added and wet mixed, and finally polyvinyl alcohol fiber and thixotropic skeleton additive are dispersed at low speed to obtain the mixture.
[0014] Correspondingly, a construction method for a solid waste gel-reinforced composite material is provided, under the conditions of nozzle diameter of 12-16 mm, pump pressure of 3.0-5.0 MPa, air pressure of 0.30-0.50 MPa, spray distance of 0.8-1.2 m, and spray angle of 90°±10°, spraying onto a vertical or top surface substrate, with a spray layer rebound rate of ≤30%, a single layer thickness of ≥30 mm, and no sagging or segregation on the surface.
[0015] The present invention has the following beneficial effects: 1) This invention parameterizes "sprayability": it provides reproducible conditions using a rheological-spraying-mechanical index chain; 2) The material coupling mechanism of this invention is clear: PC-SS reduces f-CaO, introduces carbonate cores, and slowly releases Ca. 2+ ; Aluminum source solid waste and desulfurized gypsum form an early AFt / AFm skeleton, which improves the anti-sagging effect when spraying stops; Thixotropic micro-nano skeleton provides a reconfigurable network that can quickly recover during the shearing process of pumping and spraying; 3) The invention has strong construction adaptability: it can achieve low rebound thick spraying molding under common spraying equipment and parameters. Attached Figure Description
[0016] Figure 1 The spraying characteristic parameters are for the sprayable all-solid-waste gel toughened composite materials of each embodiment and comparative example. Detailed Implementation
[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] Unless otherwise specified, the technical means used in the implementation examples are conventional means well known to those skilled in the art.
[0019] This invention discloses a toughened composite material made entirely of solid waste gel, comprising solid waste cementitious material, fine aggregate, water-reducing agent, polyvinyl alcohol fiber, and thixotropic skeleton additive. The solid waste gel material comprises pre-carbonized steel slag powder, granulated blast furnace slag, desulfurized gypsum, and aluminum-derived solid waste. The thixotropic skeleton additive is at least one of attapulgite, sepiolite, and nanocellulose (CNF).
[0020] Furthermore, the preparation process of pre-carbonized steel slag powder is as follows: the steel slag powder is subjected to gas-solid pre-carbonization treatment at 25-60℃, CO2 volume fraction of 10-100%, and for 30-180 min until f-CaO≤1.0 wt% and CO3 calculated as CaCO3. 2- The content is 8-15 wt%, which yields pre-carburized steel slag powder; the D50 of the pre-carburized steel slag powder is 2-8 μm.
[0021] Furthermore, the aluminum source solid waste is one or more of the following: calcined tap water sludge ash, calcined kaolin, and red mud fine powder. More preferably, it is calcined tap water sludge ash or red mud fine powder. The Al2O3 content in the aluminum source solid waste is 20-45 wt%. The calcined kaolin is obtained by calcining kaolin at 700-800℃ for 2.5 h, and the calcined tap water sludge ash is obtained by calcining sludge ash and red mud fine powder separately at 550-750℃ for 2.0 h, and then mixing them.
[0022] Furthermore, in the solid waste gel material, the proportions of the ingredients meet the following chemical ratio windows based on molar ratio: SO3 / Al2O3=0.8-1.4, CaO / (SiO2+Al2O3)=0.9-1.3.
[0023] Furthermore, when the thixotropic framework additive is attapulgite, its D50 is 0.2-2 μm and its specific surface area is ≥150 m². 2 / g; when the thixotropic skeleton additive is nanocellulose, its fiber diameter is 10-100 nm and its aspect ratio is ≥100.
[0024] Furthermore, based on weight per cubic meter, the total solid waste cementitious material weighs 1200-1420 kg / m³. 3 Fine aggregate 460-520kg / m³ 3 Water-reducing agent 0-20kg / m 3 Polyvinyl alcohol fiber 5-30kg / m 3 The thixotropic skeleton additive is 0.05-0.30 wt% of the total solid waste cementitious material; the total solid waste cementitious material has a D50 of 4-20 μm and a specific surface area of 400-600 m². 2 / kg. The volume fraction of the polyvinyl alcohol fiber is 0.5-3.0%, the fiber diameter is 35-40 μm, the length is 9-12 mm, and the strength is ≥1200 MPa.
[0025] Furthermore, by mass fraction, the total solid waste cementitious material contains 8-20 parts of pre-carbonized steel slag powder, 50-70 parts of granulated blast furnace slag, 15-30 parts of desulfurized gypsum, and 2-8 parts of aluminum source solid waste.
[0026] This invention employs a coupling process of pre-carbonized steel slag micro-powder (PC-SS), aluminum-sourced solid waste, and desulfurized gypsum. A specific chemical ratio window for SO3 / Al2O3 and CaO / (SiO2+Al2O3) is set and controlled by particle size and specific surface area. A thixotropic skeleton additive (at least one of attapulgite, sepiolite, and nanocellulose) is introduced to construct a reversible structural skeleton, achieving a static yield of 100-200 Pa, a plasticity of 10-30 Pa•s, and ≥80% thixotropic recovery. This results in a rebound of ≤30% and a single-layer thickness of ≥30 mm without sagging under wet spraying conditions, while maintaining a 28-day compressive strength ≥55 MPa (C55 concrete) and an ultimate tensile strain ≥3.0%.
[0027] This invention provides a method for preparing a strong and tough all-solid waste gel composite material, comprising the following steps: (1) Steel slag powder is subjected to gas-solid pre-carbonization treatment at 25-60℃, CO2 volume fraction of 10-100%, and 30-180 min until f-CaO≤1.0 wt% and CO3 calculated as CaCO3. 2- With a content of 8-15 wt%, pre-carburized steel slag powder is obtained; (2) Add granulated blast furnace slag, pre-carbonized steel slag powder, aluminum source solid waste, desulfurized gypsum and fine aggregate to the mixing pot and dry mix for 2 minutes. Then slowly pour tap water along the side wall, stir at low speed for 2 minutes and observe the state. Add water-reducing agent as appropriate to adjust the fluidity of the slurry, stir at medium speed for 3 minutes. Finally, add polyvinyl alcohol fiber and thixotropic skeleton additive at low speed, stir at low speed for 2 minutes, let stand for 3-5 minutes to degas, and obtain the mixture.
[0028] The mixture meets the following sprayability requirements: slump expansion of 140-180 mm, static yield stress of 100-200 Pa, and plastic viscosity of 10-30 Pa•s; wet spray rebound rate of ≤30% under specified spraying conditions, single-layer thickness of ≥30 mm without sagging; and 28-day compressive strength of ≥55 MPa and ultimate tensile strain of ≥3.0%.
[0029] This invention provides a construction method for a solid waste gel-based tough composite material. Under the conditions of nozzle diameter of 12-16 mm, pump pressure of 3.0-5.0 MPa, air pressure of 0.30-0.50 MPa, spray distance of 0.8-1.2 m, and spray angle of 90°±10°, the material is sprayed onto a vertical or top surface substrate. The rebound rate of the sprayed layer is ≤30%, the single layer thickness is ≥30 mm, and there is no sagging or obvious segregation on the surface.
[0030] The all-solid-waste gel-reinforced composite material provided by this invention can be used in two applications. One is for slope protection, where mesh is not required; the composite material prepared by this invention is directly sprayed, with a spray thickness of 3-5 cm, aiming to repair the surface. The other is for tunnel construction, using a combination of mesh and spraying, with a spray thickness reaching 30-50 cm. Of course, spraying is only one option. These two applications are merely illustrative of the use cases for the material prepared by this invention and should not be construed as limiting the application scenarios of the all-solid-waste gel-reinforced composite material prepared by this invention.
[0031] The present invention will be further described below with reference to specific embodiments.
[0032] Raw material requirements are: PC-SS: pre-carbonized with CO2, f-CaO ≤ 1.0 wt%, CO3 2- (Calculated as CaCO3) 8-15wt%, D50=2-8 μm; Aluminum source solid waste: roasted tap water sludge ash or red mud fine powder, Al2O3 (effective) 20-45 wt%; Slag: granulated blast furnace slag, D50=4-20 μm; Desulfurized gypsum: dihydrate or hemihydrate; Thixotropic skeleton additive: attapulgite (D50=0.2-2μm, specific surface area ≥150 μm) 2 / g) or CNF (diameter 10-100 nm); Fiber: PVA, diameter 35-40 μm, length 9-12 mm; Fine aggregate: 70-200 mesh quartz sand; Water reducing agent: polycarboxylate.
[0033] PC-SS pre-carbonization process: Steel slag powder is placed in a closed reactor and continuously introduced at 25-60 ℃ with CO2 (10-100%) for 30-180 min; during this period, samples are taken every 30 min to measure f-CaO (verified by alcohol-glycerol method or XRD / thermal analysis), and the process is stopped when the target is reached; then the reactor is cooled and sealed for later use.
[0034] The preparation process is as follows: dry mixing (slag + PC-SS + aluminum source solid waste + desulfurized gypsum + fine aggregate) for 2 min → adding water / water reducing agent at low speed for 2 min → medium speed for 3 min → adding thixotropic skeleton additive and PVA at low speed for 2 min → degassing on a vibrating table for 3-5 min.
[0035] Wet spraying tests were then conducted: nozzle 14 mm; pump pressure 3.5-4.5 MPa; air pressure 0.35-0.45 MPa; spray distance 1.0-1.2 m; spray angle 90°±10°; substrate surface saturated and dry. Rebound rate (collected and weighed), single-layer thickness spray limit, and whether sagging occurred were measured.
[0036] The basic proportioning parameters and results for each embodiment are shown in Tables 1-3 and Figure 1As shown in the table. The thixotropic agents in the table refer to different types of thixotropic skeleton auxiliaries.
[0037] Table 1 Basic proportion parameters
[0038] Table 2 Differences between the Examples and Comparisons
[0039] Table 3 Results of Examples and Comparative Examples
[0040] The test results in Tables 2 and 3 show that: The compression strength of the all-solid-waste gel-reinforced composite material (Example 1) is close to that of traditional cement-based gels, both reaching the C55 concrete grade. However, its tensile properties and spray thickness are far superior to those of traditional cement-based gel materials (Comparative Example 1). Therefore, the all-solid-waste gel-reinforced composite material provided by this invention can replace traditional cement in the preparation of gel-reinforced composite materials, realizing the reuse of solid waste and energy conservation and emission reduction.
[0041] By comparing Examples 5-7, it was found that removing the thixotropic skeleton additive, removing pre-carbonization, and removing aluminum source solid waste respectively could not simultaneously meet the three compliance thresholds; Example 4 showed that whether using attapulgite clay or cellulose CNF, as long as the chemical ratio window + pre-carbonization + thixotropic skeleton additive are met, compliance can be achieved; Example 9 showed that excessive thixotropic skeleton additive can cause pumping pressure drop and pressure fluctuation.
[0042] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A robust composite material made entirely of solid waste gel, characterized in that: The product includes solid waste cementitious materials, fine aggregates, water-reducing agents, polyvinyl alcohol fibers, and thixotropic skeleton additives. The solid waste cementitious materials include pre-carbonized steel slag powder, granulated blast furnace slag, desulfurized gypsum, and aluminum-sourced solid waste. The thixotropic skeleton additives are at least one of attapulgite, sepiolite, and nanocellulose. The pre-carburized steel slag powder contains f-CaO ≤ 1.0 wt% and CO3 calculated as CaCO3. 2- The content is 8-15 wt%, and the D50 is 2-8 μm; the Al2O3 content in the aluminum source solid waste is 20-45 wt%. The total solid waste cementitious material weighs 1200-1420 kg / m³. 3 Fine aggregate 460-520kg / m³ 3 0 < water-reducing agent ≤ 20 kg / m³ 3 Polyvinyl alcohol fiber 5-30kg / m 3 The thixotropic skeleton additive is 0.05-0.30 wt% of the total solid waste cementitious material; the D50 of the total solid waste cementitious material is 4-20 μm, and the specific surface area is 400-600 m². 2 / kg; the volume fraction of the polyvinyl alcohol fiber is 0.5-3.0%, the fiber diameter is 35-40 μm, the length is 9-12 mm, and the strength is ≥1200MPa; In the solid waste cementitious material, the molar ratio of SO3 / Al2O3 is 0.8-1.4, and the ratio of CaO / (SiO2+Al2O3) is 0.9-1.
3. When the thixotropic framework additive is attapulgite, its D50 is 0.2-2 μm and its specific surface area is ≥150 m². 2 / g; when the thixotropic framework additive is nanocellulose, its fiber diameter is 10-100 nm and its aspect ratio is ≥100; By mass fraction, the total solid waste cementitious material contains 8-20 parts of pre-carbonized steel slag powder, 50-70 parts of granulated blast furnace slag, 15-30 parts of desulfurized gypsum, and 2-8 parts of aluminum source solid waste.
2. The all-solid waste gel-reinforced composite material according to claim 1, characterized in that: The aluminum source solid waste is one or more of the following: calcined tap water sludge ash, calcined kaolin, and red mud fine powder; wherein, the calcined kaolin is obtained by calcining kaolin at 700-800℃ for 2.5h, and the calcined tap water sludge ash is obtained by calcining sludge ash and red mud fine powder at 550-750℃ for 2.0h respectively, and then mixing them together.
3. A method for preparing a solid waste gel-reinforced composite material according to any one of claims 1-2, characterized in that: Includes the following steps: (1) Steel slag powder is subjected to gas-solid pre-carbonization treatment at 25-60℃, CO2 volume fraction of 10-100%, and 30-180 min until f-CaO≤1.0 wt% and CO3 calculated as CaCO3. 2- With a content of 8-15 wt%, pre-carburized steel slag powder is obtained; (2) The granulated blast furnace slag, pre-carbonized steel slag powder, aluminum source solid waste, desulfurized gypsum and fine aggregate are dry mixed, then water and water-reducing agent are added and wet mixed, and finally polyvinyl alcohol fiber and thixotropic skeleton additive are dispersed at low speed to obtain the mixture.
4. A construction method for the all-solid waste gel-reinforced composite material prepared by the preparation method according to claim 3, characterized in that: Under the conditions of nozzle diameter of 12-16 mm, pump pressure of 3.0-5.0 MPa, air pressure of 0.30-0.50 MPa, spray distance of 0.8-1.2 m, and spray angle of 90°±10°, the sprayed layer is applied to a vertical or top surface substrate with a rebound rate of ≤30%, a single layer thickness of ≥30 mm, and no sagging or segregation on the surface.
Citation Information
Patent Citations
All-solid waste jet mortar and preparation method thereof
CN116354682A
Method for preparing high-strength concrete from all-solid waste cementing material
CN119409467A
Method for preparing solid waste cementing material from micro-carbonized steel slag
CN119707328A
